Why is Chasmanthe spp. absent from the archaeological record of the south-western Cape? - Hesse, Heidi (Department of Biological Sciences, 2017)
In the archaeological record of the south-western Cape one finds corm residues in deposits mostly in the form of the netting which surrounds the corm. These plant residues seem to be a widespread feature in the archaeological record of Later Stone Age sites in Southern Africa. Corm residues nave been identified as mainly representative of the Iridaceae family. The most common geophyte corms identified are those of Watsonia, Babiana, Hexaglottis, Moreae and Gladiolus. Interestingly, Chasmanthe spp. commonly found growing on the west coast, have not been found in archaeological deposits of this area. The carbohydrate-rich corms follow seasonal growth patterns and mainly flowering in spring and early summer and growing during the winter months. Hunter-gatherers must have been familiar with their growth patterns and their palatability so that they could exploit these plants when corms were at their optimum and harvest them before the stored carbohydrates were used up by the plant. Utility plant indices for varying plant-resource components and mineral content analysis for N, P and total non-structural carbohydrates of the corms were calculated. From the results it appears that the reason for Chasmanthe spp. not appearing in the archaeological record is due to choices made by foragers regarding field processing of low utility plant parts (i.e. plant waste), rather than its relative importance or more precisely lack thereof, in the diets of early foragers.